Analisis Pengaruh Investasi, Tenaga Kerja dan Belanja Pemerintah Daerah terhadap Pertumbuhan Ekonomi Kabupaten/Kota di Provinsi Sulawesi Tenggara - Teguh Permana; Andriani Puspitaningsih (Journal of State Economic Research, 2025)
This study aims to examine the effects of investment, labor, and regional government expenditure on economic growth at the regency/city level in Southeast Sulawesi Province during the 2021–2023 period. The data used are panel data obtained from official publications of Statistics Indonesia (BPS). The analysis was conducted using the panel data regression method with a Fixed Effect Model (FEM) approach, selected based on the results of the Chow, Hausman, and Lagrange Multiplier tests as the most appropriate model. The estimation results indicate that regional government expenditure has a positive and significant effect on economic growth, while labor and investment have positive but insignificant effects. These findings suggest that improving the effectiveness of regional government spending plays an important role in accelerating economic growth in Southeast Sulawesi. Meanwhile, the contribution of labor remains limited due to low productivity in some areas. Therefore, it is necessary to enhance productive investment and ensure more efficient management of regional expenditures to support sustainable economic growth.